Developing a scale measuring the doctor–patient relationship in China from the perspective of doctors. (13th November 2021) - Tao, Siyi; Liu, Chaojie; Wu, Qunhong; Zhao, Juan; Xue, Yuxin; Song, Weijian; Sun, Minglei; Wang, Chen; Zou, Dandan; Liu, Wei; Hao, Yanhua; Jiao, Mingli; et al.
Abstract: Objectives: The doctor–patient relationship is usually measured in line with patient needs and demands. This study aimed to develop a scale measuring such a relationship from the perspective of doctors. Methods: A draft scale was developed and adapted to the hospital context of China based on several existing scales, with an intention to measure how medical doctors view and manage their relationship with patients beyond episodic clinical encounters. Two rounds of Delphi consultations involving 14 experts were conducted to seek their consensus on the inclusion and descriptions of items. This resulted in a 19-item scale measuring four domains of the relationship. The scale was validated through a survey of 1, 712 medical doctors selected from 27 public hospitals in Heilongjiang province of China. The internal consistency of the scale was assessed using Cronbach's α coefficients of the four domains. Confirmatory factor analyses were performed to test the construct validity of the scale. Linear regression analyses were performed to assess the known-group validity of the scale. Results: The scale measures four domains. The Cronbach's α of the scale reached an acceptable level, ranging from 0.61 to 0.78 for its four domains. Good fitness of data into the four-domain structure of the scale was confirmed by the confirmatory factor analysis. Known-group differences were demonstrated in the regression analyses. Conclusion: The doctor–patient relationship scale developed in this study is a psychometrically valid tool assessing how medical doctors view and manage their relationship with patients in the hospital setting in China.